Carbon profiles of remote Australian Indigenous communities: A base for opportunities. (July 2016) - Stewart, J.; Anda, M.; Harper, R.J.
Abstract: A decision-making model was constructed to assist remote Australian Indigenous communities select appropriate climate change mitigation programs. The Resilient Community and Livelihood Asset Integration Model (ReCLAIM) comprises six steps that focus on community assets and aspirations. The second of these steps is to determine the baseline carbon profiles of communities based on six sources of carbon emissions: materials, construction processes, stationary energy, transport, water systems and waste. The methodology employed an annualised lifecycle analysis of housing materials and construction, and an annual inventory of other emission sources. Profiles were calculated for two remote communities and compared to the Australian average and also average electricity consumption by remote communities in the Northern Territory. The results, expressed in tonnes of carbon dioxide equivalent (tCO2 -e), showed that average household carbon profiles of the two communities (6.3 and 4.1 tCO2 -e/capita/yr) were generally lower than the Australian average (7.3 tCO2 -e/capita/yr). The stationary energy results revealed that infrastructure and building design could raise fuel consumption and costs, and therefore carbon emissions, despite modest lifestyles. The carbon emission categories differed between the two communities highlighting the need for an individualised approach to understanding the drivers of carbon emissions and mitigation responses. Highlights: We model carbon profiles of two remote Aboriginal communities. Community carbon profiles were lower than the Australian average. We compare stationary energy with a 72-community sample average. Low-carbon communities are possible with renewable energy systems. Building design and energy source can impact significantly on emissions.